2020
DOI: 10.1016/j.heliyon.2020.e05709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pomegranate (Punica granatum L) peel powder meal dietary supplementation on antioxidant status and quality of breast meat in broilers

Abstract: This study examined the antioxidant status and quality of breast meat in broiler birds fed diets supplemented with pomegranate peel powder meal (PPPM). During the 35-d feeding trial, broiler birds were fed six experimental diets: diet with 0% additives (negative control; NEGCON); diet with α-Tocopherol acetate at 200 g/tonne (positive control; POSCON); and four levels (2, 4, 6 and 8 g/kg) of PPPM, designated as PPPM 2 , PPPM 4 , PPPM 6 , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…The phenolic compounds of herbal products directly cleanse free radical species and improve the cell’s other defense systems, which activate antioxidant enzymes such as SOD and CAT in the body and increase antioxidant defense. Generally, it has been suggested that hepatic antioxidant enzymes such as SOD and CAT play an important role in oxidative stress protection, and these enzymes catalytically scavenge ROS in tissue, thereby increasing endogenous health mechanisms [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic compounds of herbal products directly cleanse free radical species and improve the cell’s other defense systems, which activate antioxidant enzymes such as SOD and CAT in the body and increase antioxidant defense. Generally, it has been suggested that hepatic antioxidant enzymes such as SOD and CAT play an important role in oxidative stress protection, and these enzymes catalytically scavenge ROS in tissue, thereby increasing endogenous health mechanisms [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to have a detailed understanding of the physical and chemical properties (e.g., pH, color), as well as the storage quality of meat to determine the quality of meat after slaughtering ( 34 ). The pH value of meat is an essential factor that influences the color, tenderness, cooking loss, shelf-life, and other physicochemical properties ( 35 ). After slaughtering, the breakdown of glycogen in the muscles results in the accumulation of a large amount of lactic acid which led to a pH reduction of the meat to an ultimate pH value at 24 h ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pomegranate peel is a promising feedstock for second generation ethanol production (Demiray et al, 2018). On the basis of one study, 2 g/kg supplementation of pomegranate peel powder meal may improve the water binding capacity of broiler breast meat because of reduced cooking loss of the meat (Akuru et al, 2020). Pomegranate peel and seed methanolic extracts have notable total flavonoid and phenolic contents and also antioxidant activity, which can protect the liver against histo-pathological and some enzymatic changes induced by the Methotrexate (MTX) in rats (Doostan et al, 2019).…”
Section: Pomegranate Nutritional Composition and Chemical Constituents Pomegranate Nutritional Composition And Chemical Constituents Pomementioning
confidence: 99%